â€œPOHACIâ€ SEBUAH ABSTRAKSI KARYA DARI SERAT CARIOS DEWI SRI - Hartanto Hartanto (Institut Seni Indonesia Surakarta, 2013)
The 50 page study of the work of art entitled Pohaci by Hartanto, S. Sn., M. Sn., 2012, wassponsored by a grant from DIPA ISI Surakarta in 2012. Pohaci is a dance which was inspired bythe story of Dewi Sri or Nyai Pohaci Sanghyang Sri, a tale about the rice goddess, from West Java.This work takes the figure of Dewi Sri as a reflection of Javanese women with their characteristicsof elegance, beauty, gentleness, grace, kindness, and all the perfection of a woman. The dance lastsfor 27 minutes and is presented as a new dance form. The problem addressed in the study is howthe story of Pohaci Sanghyang Sri is treated with a new or different concept and how it is interpretedin the dance. The aim of this research is to present an abstraction of the figure of a womanand to provide substance for the new work in the form of a bedhayan. It also aims to increaseknowledge and add to the existing repertoire of dances that are based on literary works. Themethod used for answering the questions includes a method of interpretation and a method ofconstruction. The method of interpretation uses an approach which interprets various elements ofthe treatment such as the content and form, the movements, music, costumes and make-up, andalso the lighting. The method of construction is a way for implementing an activity of creating awork of art, beginning by planning the movements and continuing until the work is completed.The results of the study show that the dance Pohaci is not based on the actual storyline of DewiSri but rather on the figure of Dewi Sri herself who is likened to the figure of a Javanese woman.The work is presented in the form of a bedhayan and uses 7 female dancers, accompanied bymusic played on the Javanese gamelan.